2009
DOI: 10.1002/hep.22703
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virological response reduces incidence of onset of type 2 diabetes in chronic hepatitis C†

Abstract: Diabetes is present in patients with chronic hepatitis C virus infection. The aim of this retrospective cohort study was to assess the cumulative development incidence and predictive factors for type 2 diabetes after the termination of interferon therapy in Japanese patients positive for hepatitis C virus (HCV). A total of 2,842 HCV-positive patients treated with interferon (IFN) monotherapy or combination therapy with IFN and ribavirin were enrolled. The mean observation period was 6.4 years. An overnight (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
189
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(196 citation statements)
references
References 35 publications
6
189
0
1
Order By: Relevance
“…32,33 Given the effect of IR on fibrosis progression and risk of hepatocellular carcinoma, there is a rationale for reducing IR in patients with chronic hepatitis C. SVR has been associated with reduced risk of glucose metabolism disturbances during posttreatment follow-up. 2,3 Therefore, one of the best approaches to managing IR is to eradicate HCV infection. However, as discussed above, patients with IR are less likely to respond to peginterferon/ribavirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Given the effect of IR on fibrosis progression and risk of hepatocellular carcinoma, there is a rationale for reducing IR in patients with chronic hepatitis C. SVR has been associated with reduced risk of glucose metabolism disturbances during posttreatment follow-up. 2,3 Therefore, one of the best approaches to managing IR is to eradicate HCV infection. However, as discussed above, patients with IR are less likely to respond to peginterferon/ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Proposed mechanisms for HCV-related IR and diabetes mellitus include direct hepatic effects [4][5][6] and potential contributions from extrahepatic organs. 7,8 In HCV-infected patients, IR appears to influence disease progression and response to treatment with peginterferon alpha and ribavirin.…”
mentioning
confidence: 99%
“…The mechanisms of the impact of obesity and potential beneficial role of weight loss on response to IFN bases CRC therapy have not been clearly defined. Possible mechanisms include the effect on hepatic steatosis [25][26][27][28][29][30], insulin resistance and altered immune response. Weight management has been shown not only to a decrease in steatosis but also improvement in fibrosis severity [25,26].…”
Section: Effect Of Weight Loss On Early Virological Responsementioning
confidence: 99%
“…Several observational studies have demonstrated that successful treatment of HCV with IFN/Ribavirin leads to improved insulin sensitivity and may reduce the long-term risk of type 2 diabetes [10,[13][14][15]. Tahrani et al reported a case of improved glycemic control and hypoglycemic episodes requiring cessation of diabetes therapies during treatment with IFNaRibavirin (Table 2) [16].…”
Section: Hcv Treatment Insulin Resistance and Glycemic Controlmentioning
confidence: 99%
“…Several observational studies have demonstrated that eradication of HCV is associated with improved insulin sensitivity and may reduce the long-term risk of diabetes in this population [13][14][15]. Case reports have described improvements in glycemic control with treatment of HCV with both IFN/Ribavirin and IFN/Ribavirin/telaprevir; however, the improvements were limited to the treatment phase [16,17].…”
Section: Introductionmentioning
confidence: 99%